O papel legitimador de percepções de justiça na relação entre o sexismo e a violência contra as mulheres - Paiva, Tamyres Tomaz (2022)
Violence against women is one of the most severe expressions of subjugation to which social minorities are subjected. In this work, we hypothesized that societal sexism influences the support for violence against women in marital relationships and that this influence is facilitated by a legitimation process that involves the perception of justice, particularly the limitation of the scope of justice and the belief in a just world. To this end, we developed a research program in which we conducted nine studies, which are summarized in three empirical articles. In the first article (N = 922), we conducted four studies in which we developed and validated the Acceptance of Violence Against Women Scale (AVAWS), which assesses the social acceptability of violence against women in domestic violence scenarios. The results showed that this scale has a bi-factor structure and proved suitable for evaluating people's support to five types of violence. In the second article (N = 314), we conducted a study to test the hypothesis that refusing to apply basic principles of justice to marital relationships (restricting the scope of justice) contributes to legitimizing support for violence against women. We also predict that this process occurs among university students who strongly believe that the world is a just place to live. Results showed that the relationship between sexism and narrowing the scope of justice was mediated among participants with high BJW. In the third article (N = 1,579), we conducted four experimental studies in which we demonstrated thatsocietal sexism influences support for violence against women and that this influence is mediated by the restriction of the scope of justice, but this phenomenon only occurred in participants with a low general BJW, but not in those with personal BJW. However, when general BJW was experimentally manipulated, narrowing the scope of justice was positively related to the acceptance of violence. In summary, people who are in a sexist context and are confronted with the misfortune of domestic violence tend to endorse this violence because they easily restrict their justice scope, i.e., they follow the adage, "a quarrel between husband and wife is no one's business". We discussed these findings considering theories on the processes of legitimation of social inequalities, especially within the framework of the justified discrimination model and the just-world theory.